2013
DOI: 10.1177/0898264313488165
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Disability in a Late Middle-Aged Population of Women

Abstract: Objectives This study estimates the prevalence of disability among late middle-aged women and identifies important correlates of disability among this population. Methods Disability was assessed among 376 participants of the Michigan Study of Women’s Health Across the Nation cohort at the 2011 follow-up using the World Health Organization Disability Assessment Scale. Demographic and health measures were related to disability status using logistic regression models (none or mild vs. moderate, severe or extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
1
30
1
Order By: Relevance
“…In that study, 65.2% endorsed presence of any amount of mobility disability, and 39.0% endorsed moderate to severe mobility disability. (16) However, their sample comprised a higher proportion of racial and ethnic minorities and women of low socioeconomic status than did ours; these two groups tend to have higher rates of mobility disability than the general population. (17) While prevalence of mobility disability is similar in the two samples, it is possible that in a more socioeconomically representative sample of OC survivors the prevalence of mobility disability would be even higher than present in our sample, given the symptom burden present in OC survivors.…”
Section: Discussioncontrasting
confidence: 50%
“…In that study, 65.2% endorsed presence of any amount of mobility disability, and 39.0% endorsed moderate to severe mobility disability. (16) However, their sample comprised a higher proportion of racial and ethnic minorities and women of low socioeconomic status than did ours; these two groups tend to have higher rates of mobility disability than the general population. (17) While prevalence of mobility disability is similar in the two samples, it is possible that in a more socioeconomically representative sample of OC survivors the prevalence of mobility disability would be even higher than present in our sample, given the symptom burden present in OC survivors.…”
Section: Discussioncontrasting
confidence: 50%
“…Nevertheless, the clear importance of identifying and treating diabetes in polyneuropathy is further emphasized by this study, especially as world populations are shifting to older and heavier weight demographics with increased prevalence of diabetes. 27 Our results not only further emphasized that polyneuropathy is disabling, [11][12][13][14][15]35 but also provided new insights that polyneuropathy was independently associated with greater pain and prescription of analgesics, increased lower limb complication rates (including ulcers, 20.4%, and amputations, 4.1%), greater impairment of most ADLs, higher fall tendency, stair climbing difficulty, and reliance on assistive devices or assistance from others. The degrees of impairment associations were often striking with ORs frequently greater than 3.0 even after correction for the associated multiple Charlson comorbidities.…”
mentioning
confidence: 80%
“…1 Previous studies assessing polyneuropathy prevalence [2][3][4][5][6][7][8][9][10] or disease burden [11][12][13][14][15] have focused on specific polyneuropathy subtypes or used small cohorts with limited demographics. From those studies, certain polyneuropathies have been suggested to have substantial disease burden from physical impairments 16,17 or even mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…White men have been found to be least likely to have a disability, while black and Hispanic women were most likely [45]. Other studies have found that non-Hispanic blacks and Mexican-Americans were significantly more likely to report a disability than were non-Hispanic white men and women [35], while African American women were significantly more likely to have a disability compared to white women [31]. …”
Section: Introductionmentioning
confidence: 99%